PROGRAM ECO-MASJID DENGAN BUDIDAYA KANGKUNG DARAT DI MASJID BAITUL IZZAH KECAMATAN PUJUD - Nurdin; Zulkifli; Shalahuddin; Imam Suprayogi (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract The Great Mosque of Baitul Izzah which stands majestically in Pujud District stands on a land area of ​​approximately 80 x 75 m² with a building area of ​​30 x30 m². The area of ​​this mosque is next to the kelurahan complex and on the side of the Pujud – Dalu-dalu causeway. The potential development of the EcoMasjid at the Baitul Izzah Grand Mosque in Pujud District can be realized by cultivating leafy vegetables, in this case kale cultivation is very possible to do by utilizing the mosque's gharim, administrators, mosque youth and potential congregation groups. . The way to realize EcoMasjid is to provide facilities and infrastructure in the form of providing planting media, procurement of superior seeds and skilled workers in conducting counseling and assistance in cultivating kale so as to produce maximum business results. Management of the mosque yard through reforestation by planting vegetable crops has been realized by cultivating kale. This spinach cultivation shows a beautiful view as a learning tool for the congregation who wants to see firsthand the processing, planting, growing and harvesting processes in the field. The proceeds from the sale of kale cultivation can be used as basic capital for the continuation of kale cultivation for the next stage and can be used as additional mosque operational funds to meet the needs of the gharim. Spinach cultivation has proven to be the forerunner of the Eco-Mosque model of religious tourism in this mosque. Abstrak Masjid Besar Baitul Izzah yang berdiri megah di Kecamatan Pujud berdiri diatas tanah kira-kira 80 x 75 m² dengan luas bangunan dalam 30 x30 m². Kawasan masjid ini berada disamping komplek kecamatan dan dipinggir jalan lintas Pujud - Dalu-dalu. Pengembangan potensi EcoMasjid di Masjid Besar Baitul Izzah Kecamatan Pujud dapat diwujudkan dengan budidaya tanaman sayur-sayuran kelompok daun-daunan dalam hal ini budidaya kangkung sangat mungkin untuk dilakukan dengan memanfaatkan takmir masjid, pengurus, remaja masjid dan kelompok jemaah yang potensial. Metode dalam mewujudkan EcoMasjid adalah dengan menyediakan sarana dan parasarana berupa penyediaan media tanam, pengadaan bibit yang berkualitas dan tenaga terampil dalam melakukan penyuluhan dan pendampingan dalam pembudidayaan kangkung tersebut sehingga menghasilkan hasil usaha yang maksimal. Pengelolaan pekarangan Masjid melalui penghijauan dengan budidaya tanaman sayur-sayuran telah diwujudkan dengan budidaya kangkung. Budidaya kangkung ini memperlihatkan pemandangan yang indah sebagai sarana pembelajaran bagi jemaah yang ingin melihat proses pengolahan, penanaman, proses tumbuh maupun pemanenan secara langsung dilapangan. Penjualan hasil panen budidaya kangkung ini dapat digunakan sebagai modal dasar untuk kelanjutan budidaya kangkung untuk tahap selanjutnya dan dapat digunakan sebagai tambahan dana operasional masjid untuk memenuhi kebutuhan takmir/garim. Pembudidayaan kangkung terbukti sebagai Model Eco-Masjid cikal bakal objek wisata religi di Masjid ini